Beeswax Luminaires: Sustainable lighting through materials design - Kwon, Junpyo; Asa, Pelin; Jaffar-Bandjee, Mourad; Amini, Shahrouz; Fratzl, Peter; Dierichs, Karola (Materials and Design, 2025)
Biogenic materials like beeswax have potential for sustainable manufacturing by reducing environmental impact. This study introduces “Beeswax Luminaires”, a sustainable lighting solution made from natural beeswax and water via ice-casting. The objectives are to characterize beeswax properties, optimize luminaire design for mechanical strength and light diffusion, and develop scalable robotic fabrication. Results indicate that beeswax maintains rigidity up to 50 °C and possesses suitable translucency for lighting. Parametric modeling produced corrugations enhancing flexural rigidity and light diffusion uniformity. Robotic fabrication precisely controlled coating thickness and quality, reducing product defects. Life-cycle assessment showed the production was energy-efficient, consuming less energy than traditional methods. These findings support Beeswax Luminaires as an eco-friendly lighting option, combining sustainability, optimized design and efficient manufacturing.
Keywords: Beeswax; Biogenic materials; Computational design; Light diffusion; Lighting designs; Lighting solutions; Materials design; Property; Robotic fabrications; Sustainable manufacturing; Beeswax; Biomaterials; Computational design; Lighting design; Robotic fabrication; Sustainability